A Systematic Review of Intra-Articular Hyaluronic Acid, Corticosteroids, and Platelet Rich Plasma Injections on Gait Biomechanics in Knee Osteoarthritis - Hamidreza Aslani; Fateme Mirzaee; Fatemeh Bahramian; Atefeh Aboutorabi; Alireza Jalali; Bahareh Ahmadinejad (Journal of the Dow University of Health Sciences)
The purpose of this systematic review was to assess the consequences of injections of corticosteroid (CS), hyaluronic acid (HA), and platelet-rich plasma (PRP) on gait metrics in patients with osteoarthritis (OA). We examined through the Cochrane library, SCOPUS, Web of Science, and PubMed to find pertinent publications that evaluated the effects of CS, HA, and PRP injections on gait parameters in patients with OA of the knee. Utilizing the Physiotherapy Evidence Database (PEDro) scale, quality evaluation was put into practice. A total of 15 publications with 11 randomized control trials based studies describing results for 1160 participants were published. The combined data for velocity showed a significant change with HA injection (SMD: 0.28 95% CI 0.04 to 0.53). In comparison to the control group, the HA injection group's stride length was longer, however the disparity was not statistically significant (SMD: 0.16 95% CI -0.09 to 0.4). No statistically significant differences were observed between the HA and control groups for the other variables. Results demonstrated a significant increase in knee range of motion after CS injection compared to placebo control (MD= 1.70 95% CI -0.03° to 3.37°) and without intervention. There is insufficient data to conclude that PRP and CS have a greater therapeutic advantage than one another in terms of participants' gait. Nonetheless, no intervention is supported by available data, HA is still thought to be more effective than a placebo. To find out how well therapeutic injections affect patients with knee OA's function and gait, more research is needed.